Considering Destructive Interparental Conflict and Intimate Partner Abuse: Is there a Difference?. (6th April 2018) - Kopystynska, Olena; Beck, Connie J.
Abstract : Building on existing evidence that destructive interparental conflict and intimate partner abuse (IPA) share research methodology and predict the same adjustment difficulties across numerous areas of child development, this article brings awareness to differences in terminology across disciplines and the impact these nuanced differences may have on families. We begin by identifying two main streams of scholarships followed by a discussion of research methodology similarities and differences. Important implications of differences in naming conventions for practitioners, legal and academic scholars, and victims are then discussed. Finally, we encourage professionals from both scholarships to consider referencing the other's terminology and using comprehensive assessments to better promote the well‐being of families. Key Points for the Family Court Community: To increase awareness in the naming convention of abuse across scholarly disciplines and consider the possible impact on legal professionals in how they understand family dynamics and make decisions for families To gain insight into similarities and differences of research methodological approaches measuring destructive interparental conflict and IPA To underscore the importance of using consistent terminology across fields, especially legal professionals working with victims of IPA